Carbon-ion radiotherapy in accelerated hypofractionated active raster-scanning technique for malignant lacrimal gland tumors: feasibility and safety - Akbaba, Sati; Uzun-Lang, Kristin; Held, Thomas; Herfarth, Klaus; Hörner-Rieber, Juliane; Plinkert, Peter K.; Auffarth, Gerd U.; Rieken, Stefan; Debus, Jürgen; Adeberg, Sebastian (Cancer management and research, 2019)
Carbon-ion radiotherapy in accelerated hypofractionated active raster-scanning technique for malignant lacrimal gland tumors: feasibility and safety